2008
DOI: 10.1007/s00775-008-0400-9
|View full text |Cite
|
Sign up to set email alerts
|

The ruthenium(II)–arene compound RAPTA-C induces apoptosis in EAC cells through mitochondrial and p53–JNK pathways

Abstract: An investigation of the molecular mechanism of the anticancer activity demonstrated by the ruthenium(II)-arene compound [Ru(eta(6)-p-cymene)Cl(2)(pta)] (pta is 1,3,5-triaza-7-phosphaadamantane), termed "RAPTA-C", in Ehrlich ascites carcinoma (EAC) bearing mice is described. RAPTA-C exhibits effective cell growth inhibition by triggering G(2)/M phase arrest and apoptosis in cancer cells. Cell cycle arrest is associated with increased levels of p21 and reduced amounts of cyclin E. RAPTA-C treatment also enhances… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
200
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 246 publications
(216 citation statements)
references
References 48 publications
13
200
0
3
Order By: Relevance
“…While a number of Ruthenium compounds have been tested, the prototype compound RAPTA-C has been reported to be most effective anti-cancer compound of this series and has been used extensively against a number of murine cell lines. Chatterjee S et al studied the effect of RAPTA-C induced apoptosis in EAC cells isolated from peritoneal cavity of tumor bearing mice and found that the apoptosis was dose dependent (Chatterjee S et al, 2008). In the present studies, the effect of compound has also been found to be dose dependent.…”
Section: IIIsupporting
confidence: 63%
See 1 more Smart Citation
“…While a number of Ruthenium compounds have been tested, the prototype compound RAPTA-C has been reported to be most effective anti-cancer compound of this series and has been used extensively against a number of murine cell lines. Chatterjee S et al studied the effect of RAPTA-C induced apoptosis in EAC cells isolated from peritoneal cavity of tumor bearing mice and found that the apoptosis was dose dependent (Chatterjee S et al, 2008). In the present studies, the effect of compound has also been found to be dose dependent.…”
Section: IIIsupporting
confidence: 63%
“…In the present studies, the effect of compound has also been found to be dose dependent. In a similar study, flow cytometry analysis of RAPTA-C induced cell cycle phase distribution of nuclear DNA has shown increased content of haploid DNA in RAPTA-C treated cells (Chatterjee S et al, 2008). However, the DNA in S-phases decreased from 6.3 to 3.6 % suggesting that tumor suppressor gene P 53 is central to the induction of cell cycle arrest and apoptosis in response to DNA damage of cellular stage in human cells.…”
Section: IIImentioning
confidence: 91%
“…Indeed, several ruthenium-containing drugs interact with DNA and modify its structure, suggesting that they might induce DNA damages. Activation of p53 or p73 by some of these drugs partly corroborated this hypothesis (23)(24)(25). Alternative modes of action have also been described, including production of reactive oxygen species (26), inhibition of kinases (27), modification of enzymatic activities (28), or redox reactions (29).…”
Section: Introductionmentioning
confidence: 72%
“…However, the mechanisms of action of ruthenium-based anticancer compounds are comparatively unexplored, although it is clear that ruthenium compounds interact far more weakly with DNA relative to platinum compounds [15]. There is evidence to suggest that ruthenium compounds might directly interfere with specific proteins involved in signal transduction pathways and/or alter cell adhesion and migration processes [10,16,17].…”
Section: Introductionmentioning
confidence: 99%